Viewing agricultural water management through a systems analysis lens - Zhu, Tingju; Rosegrant, Mark W.; Ringler, Claudia (American Geophysical Union, 2019)
Appropriate agricultural water management (AWM) is crucial not only for alleviating water scarcity but also for food and nutrition security and healthy ecosystems. The multi‐dimensional nature of AWM and inherently complex feedbacks between its components necessitate a systems approach. This paper proposes six dimensions of AWM and illustrates the importance of a systems approach using six separate, but linked, classical AWM topics. By emphasizing the whole picture of AWM and interactions among its sub‐systems at multiple levels, a systems approach offers the opportunity to holistically scrutinize the pros and cons of proposed AWM interventions beyond their direct effects at the locus that a single dimensional approach foretells.